2009
DOI: 10.1007/s10964-009-9482-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Non-Suicidal Self-Injury and Suicide Attempts in Adolescents

Abstract: As suicide attempts and self-injury remain predominant health risks among adolescents, it is increasingly important to be able to distinguish features of self-harming adolescents from those who are at risk for suicidal behaviors. The current study examined differences between groups of adolescents with varying levels of self-harmful behavior in a sample of 373 high school students with a mean age of 15.04 (SD = 1.05). The sample was 48% female and the distribution of ethnicity was as follows: 35% Caucasian, 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
240
6
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(284 citation statements)
references
References 29 publications
14
240
6
13
Order By: Relevance
“…9,29,49 As suggested by the results of the current study, the differences in frequencies and trends of NSSI and risk behaviors justify the distinction of these two practices. 23,50 Thus, self-harm was considered in a stricter sense and a clear distinction between these behaviors was taken into account, in order to obtain a more reliable estimate of the NSSI phenomenon. Even so, the percentage of DASS-21 = Depression, Anxiety, and Stress Scale; EMWSS = Early Memories of Warmth and Safeness Scale; FSCRS = Forms of Self Criticism/Attacking and Reassuring Scale; ISSIQ-A = Impulse, Self-harm and Suicide Ideation Questionnaire for Adolescents; OAS = Other as Shamer Scale; SE = standard error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,29,49 As suggested by the results of the current study, the differences in frequencies and trends of NSSI and risk behaviors justify the distinction of these two practices. 23,50 Thus, self-harm was considered in a stricter sense and a clear distinction between these behaviors was taken into account, in order to obtain a more reliable estimate of the NSSI phenomenon. Even so, the percentage of DASS-21 = Depression, Anxiety, and Stress Scale; EMWSS = Early Memories of Warmth and Safeness Scale; FSCRS = Forms of Self Criticism/Attacking and Reassuring Scale; ISSIQ-A = Impulse, Self-harm and Suicide Ideation Questionnaire for Adolescents; OAS = Other as Shamer Scale; SE = standard error.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several studies have noted that selfharm behaviors result in suicide when untreated. [22][23][24][25] It is possible that the increased reinforcement experienced by repetitive self-harm behaviors renders individuals more capable of sustaining the pain and fear resulting from those behaviors, and thus able to perform more severe forms of self-injurious behaviors that can progressively lead to suicide. 18,26 Similarly, it is possible that suicide is an unintentional result of NSSI, 27 to the extent that a fatal consequence may result accidentally from NSSI behavior.…”
Section: 20mentioning
confidence: 99%
“…Thus, despite the important differences between NSSI and suicidal behavior, however, research has shown that these behaviors can also co-occur among clinical and community-based samples (Nock and Prinstein, 2004;Nock et al, 2006;Andover and Gibb, 2010). Several authors pointed out that self-harm is often related to suicidal ideations and attempts, and, can precede suicide if untreated (Hawton et al, 1999;Hawton, 2002;Brausch and Gutierrez, 2010;Martin et al, 2010;Hamza et al, 2012;Zetterqvist et al, 2013), constituting the main risk factor for suicide (NHS, 1998). Moreover, approximately 50-75% of those with a history of NSSI make a suicide attempt at some point (Joiner, 2005;Nock et al, 2006), further highlighting the dangerousness of this behavior.…”
Section: Nssi Suicide and Risk Behaviorsmentioning
confidence: 99%
“…NSSI has become a serious global public health concern, particularly among adolescents (Heath et al, 2008;Muehlenkamp, 2014;Muehlenkamp et al, 2012;Nock, 2010). Various studies from Asia (You and Leung, 2012), Australia (Tanner et al, 2015), Canada (Armiento et al, 2014), Europe , and the US (Sornberger et al, 2012;Brausch and Gutierrez, 2010) have found lifetime prevalence rates of NSSI among adolescent students ranges between 10-32%. Higher rates have been reported among adolescents from clinical settings ranging from 24% in Canada (Armiento et al, 2016), to 40% in Europe (Kaess et al, 2013), and 63-80% in the US (Auerbach et al, 2014;Victor et al, 2012;Weismoore and Esposito-Smythers, 2010).…”
Section: Introductionmentioning
confidence: 99%